Kajian Transformasi Fungsi Bangunan - Ratu Manieh; Danang Harito Wibowo (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2020)
This study discusses about the transformation of functions with a case study of buildings at Ara Center, located in Gading Serpong, Tangerang. Ara Center was originally designed as an apartment complex. However, during the construction process, two of the pleasant buildings that were designed underwent a process of changing into a hotel and university. The purpose of this study is to find out how the transformation that occurs in buildings that have been designed, both in the spatial system and physical and figural systems. This study also has a purpose to find out how the spatial, physical, and figural patterns that are formed to the current activities. The method used in this study is a qualitative descriptive method with a case study approach. The results of this study found that the transformation of functions that occur changes the spatial system in buildings in terms of spatial layout. Whereas in physical and figural systems only a few changes occur.